2018
DOI: 10.3892/mco.2018.1565
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of advanced lung cancer presenting as a symptomatic gastric tumor

Abstract: Abstract. Although gastric metastases have been estimated to occur in less than 2% of cancer patients, an increased use of upper digestive tract endoscopy allows for a higher detection of secondary gastric tumors. We describe the case of a 66-year-old male patient presenting with mild pain in the sternum and upper abdominal area. Physical examination revealed a right parietal skull tumor, with no other significant clinical changes. Upon exclusion of an acute coronary syndrome, upper digestive tract endoscopy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Therefore, immunohistochemistry is a reliable method to distinguish primary from metastatic gastric cancer. The commonly used markers for subtyping non-small cell lung cancer included TTF-1, CK7, Napsin A for adenocarcinoma, and p63, CK5/6, CK34βE12/CK903 for SCC (38). TTF-1 is highly specific for adenocarcinomas of pulmonary origin exhibiting a positive predictive value of 100% (2,13).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, immunohistochemistry is a reliable method to distinguish primary from metastatic gastric cancer. The commonly used markers for subtyping non-small cell lung cancer included TTF-1, CK7, Napsin A for adenocarcinoma, and p63, CK5/6, CK34βE12/CK903 for SCC (38). TTF-1 is highly specific for adenocarcinomas of pulmonary origin exhibiting a positive predictive value of 100% (2,13).…”
Section: Discussionmentioning
confidence: 99%
“…Gastric involvement in metastatic SCLC is rare [2]. Diagnosis of gastric SCLC metastases before primary disease is extremely rare [4]. In our case, the occurrence of nonspecific upper gastrointestinal symptoms with red flag signs prompted an endoscopic evaluation.…”
mentioning
confidence: 89%
“…For the third pair of networks, it has been reported that (i) gastrointestinal metastases from lung cancer are diagnosed at a late stage and are thus life threatening 53 , (ii) gastric cancer metastasis results from lung cancer 54 , (iii) gastric cancer is associated with lung cancer [55][56][57][58] , and (iv) both diseases can be successfully treated with carboplatin 59 .…”
Section: Network Similarity -Jensen-shannon Entropymentioning
confidence: 99%